2022
DOI: 10.3389/fpls.2022.953717
|View full text |Cite
|
Sign up to set email alerts
|

The regulatory role of abscisic acid on cadmium uptake, accumulation and translocation in plants

Abstract: To date, Cd contamination of cropland and crops is receiving more and more attention around the world. As a plant hormone, abscisic acid (ABA) plays an important role in Cd stress response, but its effect on plant Cd uptake and translocation varies among plant species. In some species, such as Arabidopsis thaliana, Oryza sativa, Brassica chinensis, Populus euphratica, Lactuca sativa, and Solanum lycopersicum, ABA inhibits Cd uptake and translocation, while in other species, such as Solanum photeinocarpum and B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 145 publications
0
7
0
Order By: Relevance
“…Interestingly, knockout or overexpression of the AtILR3 gene did not alter the Cd accumulation, while the ABA treatment observably increased the Cd accumulation in the roots and leaves of all plants (Figure 8B), suggesting that there appeared to be an unidentified influx transporter for the Cd in roots that were associated with ABA signalling and completely unrelated to the AtILR3 . ABA has a vital function in the Cd stress response, but the regulatory mechanism by which plants accumulate and uptake Cd remains unclear (Shen et al, 2022). Taken together, these ion accumulation patterns suggested that ABA treatment has a strong effect on ion homeostasis, implying that certain metal ions, such as Cd, play potential roles in ABA signalling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, knockout or overexpression of the AtILR3 gene did not alter the Cd accumulation, while the ABA treatment observably increased the Cd accumulation in the roots and leaves of all plants (Figure 8B), suggesting that there appeared to be an unidentified influx transporter for the Cd in roots that were associated with ABA signalling and completely unrelated to the AtILR3 . ABA has a vital function in the Cd stress response, but the regulatory mechanism by which plants accumulate and uptake Cd remains unclear (Shen et al, 2022). Taken together, these ion accumulation patterns suggested that ABA treatment has a strong effect on ion homeostasis, implying that certain metal ions, such as Cd, play potential roles in ABA signalling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The upregulated DEMs were predominantly composed of alkaloids, lipids, flavonoids, phenolic acids, organic acids, amino acids, nucleotides, and their derivatives ( Supplementary Table S7 ). Interestingly, at the early stage of Cd stress, there was a significant increase in the level of abscisic acid potentially triggering intricate stress-adaptive signaling cascades ( Shen et al., 2022 ). Additionally, melatonin was significantly upregulated at all time points ( Figure 6C ) consistent with previous findings ( Ahammed et al., 2024 ).…”
Section: Discussionmentioning
confidence: 99%
“…If heavy metals accumulate excessively in food crops, human consumption of such excess crops will cause great harm to human health. Therefore, heavy metals are essential for human food security [82][83][84][85]. Gu et al identified that the WRKY transcription factor gene ZmWRKY64 is enhanced in maize roots and leaves under cadmium stress, and that knocking down the expression of ZmWRKY64 leads to excessive cadmium accumulation in leaf and root cells, resulting in a cadmium-sensitive phenotype.…”
Section: Role Of Wrky Transcription Factors In Plant Response To Heav...mentioning
confidence: 99%